2016
DOI: 10.1242/jcs.181891
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl endopeptidase is involved in the degradation of neural cell adhesion molecules in vitro

Abstract: Membrane-associated glycoprotein neural cell adhesion molecule (NCAM) and its polysialylated form (PSA-NCAM) play an important role in brain plasticity by regulating cell-cell interactions. Here, we demonstrate that the cytosolic serine protease prolyl endopeptidase (PREP) is able to regulate NCAM and PSA-NCAM. Using a SH-SY5Y neuroblastoma cell line with stable overexpression of PREP, we found a remarkable loss of PSA-NCAM, reduced levels of NCAM180 and NCAM140 protein species, and a significant increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Our study demonstrates that MMP9 is significantly decreased in the HFD-PREP gt mice. Previous studies indicated that PREP could regulate the activity of extracellular MMP9 (29,35). Notably, the production of PGP was obviously suppressed in the HFD-PREP gt mice.…”
Section: Discussionmentioning
confidence: 87%
“…Our study demonstrates that MMP9 is significantly decreased in the HFD-PREP gt mice. Previous studies indicated that PREP could regulate the activity of extracellular MMP9 (29,35). Notably, the production of PGP was obviously suppressed in the HFD-PREP gt mice.…”
Section: Discussionmentioning
confidence: 87%
“…Jaako K et al indicate that the PST protein nucleus expression was also found in the wild-type neuroblastoma cells. 35 However, in the denervation group, the level of NCAM expression decreased during the regeneration process. In contrast, the level of PST expression increased after deligation and remained high at day 28.…”
Section: Discussionmentioning
confidence: 93%
“…THY1 (Thy-1 Cell Surface Antigen) has previously been shown to be downregulated in NP compared to AF and upregulated with age, where THY1-cell interactions can result in focal adhesion formation. 60,117 Similarly, ANGPT1, FAP (Prolyl endopeptidase FAP), CADM1, and CDON have been associated with cytoskeletal reorganization, cell-ECM and cell-cell interactions, as well as involvement in mechanosensitive intracellular signaling pathways in cell types including NP and AF cells [118][119][120][121][122][123][124][125][126][127][128][129][130]. One of the most highly enriched downregulated gene sets was Vacuolar Lumen, where many genes are associated with lysosomal activity.…”
mentioning
confidence: 99%